PROMOTING HEALTHY INTERPERSONAL RELATIONSHIP THROUGH PARTICIPATION IN SPORTS IN NIGERIA - Ugwueze, Fabian; Ugwu, Mr. Ndubuisi (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Sports activities are wonderful tools for promoting healthy interpersonal relationship for optimal health. However, literature evidence points to the fact that sports have not been adequately used to promote social health among participants in Nigeria. This is because many people. who participate in individual sports and recreational activities. like jogging. weight lifting. badminton, and other individual games, do so without having enough social interaction with other participants, thereby loosing the social benefits of sports. In this paper, efforts have been made to explain the reasons why people participate and socialise in sports; the social situation in sports participation in Nigeria, and how sports can be used to promote healthy interpersonal relationship for social cohesion, social capital and social health in Nigeria. It is on this basis that the conclusion was made.